Correlation of Serum Vitamin A Levels with Disease Activity Indices and Colonic IL‐23R and FOXP3 mRNA Expression in Ulcerative Colitis Patients. (13th July 2016) - Verma, P.; Subodh, S.; Tiwari, V.; Rampal, R.; Tuteja, A.; Toteja, G. S.; Gupta, S. D.; Ahuja, V.
Abstract: Genome‐wide association studies have identified IL‐23 receptor (IL‐23R) as a susceptibility locus for the pathogenesis of ulcerative colitis (UC), which is characterized by exaggerated Th2/Th17 response. Studies have shown that vitamin A (VA) reduces disease progression by promoting FOXP3⁺ T cells and curbing Th17 cells. In this study, we explored the association of colonic IL‐23R and FOXP3 expression in fifty‐one UC patients (23 in remission and 28 with active disease) with serum VA levels and disease activity. We observed that decreased serum VA levels were associated with increased disease activity. However, there was no significant difference in mucosal IL‐23R and FOXP3 expression in UC patients with moderate–to‐severe disease activity compared to those in remission. Also, no significant correlation was drawn between serum VA levels and mucosal IL‐23R and FOXP3 expression. Our study suggests that even after an established role of VA in inhibiting Th17 responses in mice models and humans, serum VA levels and disease activity do not correlate with FOXP3 and IL‐23R expression in colonic mucosa of UC patients.